The hepatitis C cascade of care in HIV/hepatitis C virus coinfected individuals in Europe: regional and intra-regional differences - Fursa, Olga; Mocroft, Amanda; Lazarus, Jeffrey V; Amele, Sarah; Lundgren, Jens; Matulionyte, Raimonda; Rasmussen, Line D; Rockstroh, Jürgen K; Parczewski, Milosz; Jilich, David; Moreno, Santiago; Vassilenko, Anna; et al. (AIDS (London), 2022)
Following the introduction of direct-acting antiviral therapy in 2013, WHO launched the first Global Health Sector Strategy on Viral Hepatitis. We describe a hepatitis C virus (HCV) cascade of care in people with HIV (PWH) across Europe in terms of reaching the WHO elimination targets of diagnosing 90% and treating 80% of HCV-infected individuals. HIV/HCV-coinfected participants in the EuroSIDA cohort under prospective follow-up at October 1, 2019, were described using a nine-stage cascade of care. Care cascades were constructed across Europe, on a regional (n = 5) and country (n = 21) level. Of 4773 anti-HCV positive PWH, 4446 [93.1%, 95% confidence interval (CI) 92.4-93.9)] were ever tested for HCV RNA, and 19.0% (95% CI 16.4-21.6) were currently HCV RNA positive, with the highest prevalence in Eastern and Central-Eastern Europe (33.7 and 29.6%, respectively). In Eastern Europe, 78.1% of the estimated number of chronic infections have been diagnosed, whereas this proportion was above 95% in the other four regions. Overall, 3116 persons have ever started treatment (72.5% of the ever chronically infected, 95% CI 70.9-74.0) and 2404 individuals (55.9% of the ever chronically infected, 95% CI 53.9-57.9) were cured. Cure proportion ranged from 11.2% in Belarus to 87.2% in Austria. In all regions except Eastern Europe, more than 90% of the study participants have been tested for HCV-RNA. In Southern and Central-Western regions, more than 80% ever chronically HCV-infected PWH received treatment. The proportion with cured HCV infection did not exceed 80% in any region, with significant heterogeneity between countries. In a pan-European cohort of PWH, all regions except Eastern Europe achieved the WHO target of diagnosing 90% of chronic HCV infections, while the target of treating 80% of eligible persons was achieved in none of the five regions.